Patellar Height Correlates Modestly With Trochlear Dysplasia: A Magnetic Resonance Imaging Analysis - S. Brandon Luczak, M.D; Chris Cheng, B.S; Jon P. Hedgecock, M.D; Michael Brimacombe, Ph.D; J. Lee Pace, M.D (Elsevier, 2022)
Purpose: To evaluate whether there is a correlation between the position of the patella and trochlear morphology in patients with and without patellar instability using exclusively MRI measurements. Methods: MRI scans of knees in patients with patellofemoral instability and knees of patients with an ACL (anterior cruciate ligament) tear as a control group were reviewed. Measurements of patellar position (Canton-Deschamps ratio, Patellar Trochlear Index, and lateral patellar inclination) and trochlear morphology (lateral trochlear inclination and sulcus angle) were obtained from each scan. Bivariate and multivariate analysis was performed to identify correlations between study group, demographics, and patellofemoral joint measurements. Results: There were 70 knees in the patellofemoral instability group and 60 knees in the control group. Bivariate analysis showed a significant difference in all measurements between the patellar instability group and the control group. Multivariate analysis showed modest correlations between patellar position and trochlear morphology. The Caton-Deschamps (CD) ratio correlated with patellar trochlear index (P < .001) and lateral trochlear inclination (P < .001). The respective R-square goodness of fit was 41.1%. Patellar trochlear index correlated with CD ratio (P < .001), lateral trochlear inclination (P < .001), lateral patellar inclination (P < .001), and patellar instability group (P = .011). The R-sq goodness of fit was 37.3%. Lateral patellar inclination correlated with patellar trochlear index (P < .001), Lateral trochlear inclination (P < .001), and age at first dislocation or injury (P = .02). The R-sq goodness of fit was 68.56%. Conclusions: Using MRI-based measurements of the patellofemoral joint, we identified modest, but significant, correlations between measures of patellar height (patellar trochlear index, CD ratio, and lateral patellar inclination) and trochlear dysplasia. This correlation is unclear and is likely multifactorial, but on the basis of this work, a causal relationship between trochlear dysplasia and patella alta cannot be established. Clinical Relevance: Radiographic evaluation of the patella and how it relates to the surrounding boney anatomy provides important information regarding our understanding of patella instability and its treatment.